Robotic-Assisted Complex Pulmonary Resection: Sleeve Lobectomy for Cancer. Issue 2 (March 2021) - Watkins, Ammara A.; Quadri, Syed M.; Servais, Elliot L.
The use of robotic assistance for complex pulmonary resections such as segmentectomy and sleeve lobectomy has steadily increased in recent years. These operations are technically challenging as they require fine dissection and suturing, which is often difficult to perform using traditional minimally invasive techniques. Robotic surgery is well-suited for complex pulmonary surgery given its specific advantages related to superior optics and precise tissue manipulation and dissection. Herein we describe our technique for robotic-assisted complex pulmonary surgery with a specific focus on right upper sleeve lobectomy for cancer, including associated video case demonstration. The principles discussed are generalizable to other complex lung and tracheobronchial operations and highlight the benefits of the robotic platform.